Strengthening the educational fabric: The role of school management committees in enhancing community-school partnerships in Nepal - Dahal, Bhushan (A Bi-annual South Asian Journal of Research & Innovation, 2025)
School-community partnerships play a critical role in fostering effective and sustainable education systems. This study investigates the School Management Committees (SMCs) as the sole legally mandated bridge between schools and communities in Nepal. Grounded in Epstein’s parental involvement framework, the research examines the collaborative dynamics between SMC heads and key stakeholders across six model secondary schools in Bagmati Province. Findings shows significant communication gaps, the pervasive influence of local politics, and structural barriers that hinder meaningful engagement. The study advocates for a distributed leadership approach, emphasizing the need for inclusive decision-making processes and stronger community participation in school governance. This research contributes to the broader discourse on educational management and policy reform in Nepal and comparable global contexts by offering a contextually relevant framework for strengthening school-community partnerships.